A ceRNA network-mediated over-expression of cuproptosis-related gene SLC31A1 correlates with poor prognosis and positive immune infiltration in breast cancer - Lian, Weibin; Yang, Peidong; Li, Liangqiang; Chen, Debo; Wang, Chuan (Frontiers in Medicine, 2023)
Solute carrier family 31 member 1(SLC31A1) has been reported as the copper importer, and was identified to be involved in the process of “cuproptosis”. However, the mechanism of SLC31A1 in breast cancer remains unclear. We examined the expression of SLC31A1 mRNA in breast cancer tissues and cell lines using Real-time PCR. The data for this study were obtained from The Cancer Genome Atlas (TCGA) database. TIMER, UALCAN, GEPIA2, STRING, Metascape, Kaplan–Meier Plotter, Xiantao Academy, starBase，and miRNet websites were used for a comprehensive analysis of SLC31A1. Our study suggested that SLC31A1 mRNA was over-expressed in breast tumor tissues and breast cancer cell lines, which was closely related to poor relapse-free survival (RFS) and distant metastasis-free survival (DMFS). In addition, we constructed a co-expression network of SLC31A1. Functional enrichment analysis indicated that these genes are mainly involved in copper ion transport. Our results suggested that SLC31A1 expression was positively associated with all m6A-related genes, especially with YTHDF3 (r = 0.479). Importantly, the LINC00511/miR-29c-3p/SLC31A1 axis was determined as the potential pathway driving malignant progression of breast cancer by affecting copper transport. Furthermore, our results revealed that SLC31A1 expression was positively correlated with tumor immune cell infiltration, immune cell biomarkers，and cancer-associated fibroblast（CAF）. Overall, we provide a comprehensive analysis of SLC31A1 in breast cancer. The up-regulation of SLC31A1 expression and regulation of copper ion transport mediated by the LINC00511-miR-29-3p axis is related to poor prognosis and positively correlated with tumor immune infiltration in breast cancer.